1961
DOI: 10.1111/j.1550-7408.1961.tb01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Cellular Slime Mold Acrasis rosea*

Abstract: A number of isolates of the cellular slime mold, Acrasis rosea, differed from each other in the range of microorganisms on which they could grow and fruit. In a test for the possible occurrence of sexual reproduction and genetic recombination, two of the most widely divergent of these physiological races were studied further. Mixed colonies were obtained in agar plate cultures of Rhodotorula mucilaginosa, a yeast utilized by both. When spores from mature fruiting bodies or amoebae migrating out from the mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1962
1962
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 14 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…It was not possible to test all known species, but we chose at least one representative species of each group defined by a phylogenetic tree constructed by Schaap and colleagues [5]. We also tested the effect of D. caveatum on Acrasis rosea , which, though it is amoeboid and has an aggregative developmental cycle, is unrelated to the Dictyostelia [11], [12]. Its amoebae are also ingested by D. caveatum (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…It was not possible to test all known species, but we chose at least one representative species of each group defined by a phylogenetic tree constructed by Schaap and colleagues [5]. We also tested the effect of D. caveatum on Acrasis rosea , which, though it is amoeboid and has an aggregative developmental cycle, is unrelated to the Dictyostelia [11], [12]. Its amoebae are also ingested by D. caveatum (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Although the sexual reproduction of several heterolobosean species has been discussed (e.g., Bunting, 1926;Droop, 1962;Fritz-Laylin et al 2010;Olive et al, 1961;Olive, 1963;Pernin et al, 1992), no direct evidence has been found and the nature of the putative sexual processes remains unclear. Some authors hypothesize that the amoeba is the diploid stage whereas the flagellate is haploid and represents the gamete (Droop, 1962;Fulton, 1993).…”
Section: Life Cycles Of Heteroloboseamentioning
confidence: 99%
“…The new cellular slime mold isolates are clearly in the genus of Acrasis sensu Olive and Stoianovitch (1960). The amoebae of our isolates are morphologically identical to those of A. rosea (Olive and Stoianovitch 1960;Olive et al 1961). Amoebae have a single nucleus with a large centrally located nucleolus.…”
Section: Discussionmentioning
confidence: 63%
“…Acrasis rosea was originally described to be an extremely plastic organism, in which a single isolate may display a wide variety of complexity in fruiting body morphology once in culture (Olive and Stoianovitch 1960). Later studies on variation in A. rosea increased our recognition of the diversity of the species (Olive, Dutta, and Stoianovitch 1961; Reinhardt 1968, 1975), but these studies may have been handling multiple species, which could now be delimited by modern molecular techniques.…”
mentioning
confidence: 99%